The Transformation of Sweet Potatoes into Creative Culinary Products: Training Young Entrepreneurs in Agricultural Areas - baktiawan nusanto; Kahar Haerah (Universitas Muhammadiyah Jember, 2025)
This community service activity aimed to enhance the capacity of youth in Panti Village, Jember Regency, in processing sweet potatoes into value-added food products as part of developing a creative economy based on local potential. Held on May 13–14, 2025, the program involved 15 participants and was conducted through two main methods: socialization and hands-on training. The socialization session provided insights into the economic potential of sweet potatoes, business opportunities, marketing strategies, and the strategic role of youth in rural economic development. The technical training focused on practical skills for producing and packaging sweet potato-based products such as steamed sweet potatoes, fried sweet potatoes, chips, and traditional cakes. Participants also learned about product branding and digital marketing. Evaluation results indicated a high level of participant satisfaction with both the content and the delivery methods. This initiative successfully improved participants’ knowledge, skills, and entrepreneurial motivation. It is expected to serve as a starting point for the growth of micro-businesses based on local food resources and contribute to sustainable economic development in the region